Analysis of English Text Based on Character Education: Student's Perception and Comprehension - Ikhwan Fauzi; Puspita Sari Nasution (Didaktika: Jurnal Kependidikan, 2024)
This study aims to investigate the students' perceptions and comprehension of English texts based on character education at a State Vocational. This research is descriptive using qualitative and quantitative on its approach. The research involved 40 students of class XI from the accounting/financial expertise program at SMKN 1 Tebing Tinggi and 40 students from class XI from the technical skills program at SMKN 2 Tebing Tinggi as the participants. Questionnaires and written tests were used as the instrument to collect the data. Based on the analysis of the results of the questionnaires taken in the two vocational schools, it is found that 55% of students gave positive perceptions of learning English texts based on character education, 64% agreed that character education-based English text learning materials were given in schools, 57% of students agree that learning character education will help develop attitudes. In addition, the results of the written test showed that 56% of the student were at an average level in terms of their level of understanding of character education-based English texts.